God in the Courtroom the Transformation of Courtroom Oath and Perjury Between Islamic and Franco-Egyptian Law. - Bechor, Guy. (Leiden : BRILL, 2011)
This volume compares the courtroom oaths of both Islamic and modern Egyptian legal systems, blending elements of legal history, comparative law, theology, philosophy and culture.
15. Can the Defendant Guide the Wording of the Oath in His Favor?15.1 Redemption of an oath ('iftida') as avoidance of danger; 16. A Religious Element in the Service of Law: The Intensification of the Oath; 16.1 The text; 16.2 Means of swearing on the Qur'an; 16.3 Repetition; 16.4 Way of ceremony (h?al); 16.5 The dimension of place; 16.6 The dimension of time; 16.7 Non-Muslim; 17. The Testimonial Oath; 18. Special Types of Oaths: Curses (li'an) and Qasama; 18.1 The terrible story of 'Uwaymar and his wife Khawla; 18.2 Management of the curse procedure: the ceremony.
18.3 The outcome of the curses procedure: Legal analysis.
Description based on print version record.
Keywords: Law -- Egypt -- French influences; Law -- Egypt -- Islamic infuences; Oaths -- Egypt; Oaths (Islamic law) -- Egypt; Law; Oaths -- Egypt; Oaths (Islamic law) -- Egypt; Law -- Egypt -- French influences; Law -- Egypt -- Islamic influences; LAW / Civil Procedure; LAW / Legal Services; POLITICAL SCIENCE / Government / Judicial Branch; Electronic books